KISS Berbanding Multilevel Approach - Muhammad Ali Napiah Lubis; Samrul Bahri Hutabarat (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Management is very urgent and needed in managing institutions, businesses and organizations, because without measurable management the journey of institutions, businesses and organizations will find many difficulties in achieving goals. In maximizing work as a team to achieve organizational goals, four actions are introduced in management science, namely coordination, integration, simplification and synchronization, which is abbreviated as "KISS". This research is a research that uses the method of literature study or literature review. Library and literature research, explaining the phenomenon of organization that occurs is based on scientific studies that have been done before. The KISS and Multilevel approaches are two ways of approaching transdisciplinary management which have different approaches, if the KISS approach is smaller, namely the internal side of the organization, while the multilevel approach is broader by involving all possibilities that can support the achievement of goals, starting from the highest level, middle level and lowest level. Both KISS and the multilevel approach both process for the same purpose, namely achieving organizational goals properly, effectively and efficiently.